2016
DOI: 10.4081/oncol.2016.298
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and angiotensin system inhibitors in patients with metastatic renal cell carcinoma

Abstract: Arterial hypertension (HTN) is a class effect of anti-vascular endothelial growth factor (VEGF) therapies, including the monoclonal antibody bevacizumab. Data are conflicting regarding the role of the renin-angiotensin system on angiogenesis and recent data suggest that the use of angiotensin system inhibitors (ASIs; angiotensin receptor blockers or angiotensin-converting enzyme inhibitors) is associated with improved survival in metastatic renal cell carcinoma (mRCC), particularly when used with VEGF targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 72 publications
0
17
0
2
Order By: Relevance
“…Nonetheless, in vivo studies have shown that ACEi increases release of NO and are thus recommended as rst line agents for management of anti-VEGF induced hypertension; 11 especially for their renoprotective effects given higher risk of proteinuria on VSP inhibition therapy. 12 It is possible that BP control with ACEi/ARBs in this population occurs due to angiogenesis inhibition by RAAS antagonism and not due to their direct antihypertensive action.…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, in vivo studies have shown that ACEi increases release of NO and are thus recommended as rst line agents for management of anti-VEGF induced hypertension; 11 especially for their renoprotective effects given higher risk of proteinuria on VSP inhibition therapy. 12 It is possible that BP control with ACEi/ARBs in this population occurs due to angiogenesis inhibition by RAAS antagonism and not due to their direct antihypertensive action.…”
Section: Discussionmentioning
confidence: 96%
“…Thus ACEi/ARBs can cause suboptimal BP lowering effects in cases of severe hypertension due to already suppressed RAAS in these patients. Nonetheless, in vivo studies have shown that ACEi increases release of NO and are thus recommended as first line agents for management of anti-VEGF induced hypertension [11]; especially for their renoprotective effects given higher risk of proteinuria on VSP inhibition therapy [12]. It is possible that BP control with ACEi/ARBs in this population occurs due to angiogenesis inhibition by RAAS antagonism and not due to their direct antihypertensive action.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors report the role of the renin-angiotensin system (RAS) in cancer development ( 5 7 ) but studies concerning RCC have not been comprehensively revised so far. Derosa et al ( 8 ) has publish recently review on RAS inhibitors in RCC concentrating mostly on hypertension and impact on patients survival. In this paper we present review of current knowledge about role of RAS in RCC development and progression, including not only clinical aspects but also molecular mechanisms and possible future directions in clinical and basic research in this field.…”
Section: Introductionmentioning
confidence: 99%